The Image of Social Enterprises in Czech Online Media(2013 – 2018) - Koudelková, Petra; Zavadilová, Tereza (Communication Today, 2025)
The article deals with the online versions of eight Czech news media (novinky.cz, iHNed.cz, iDnes.cz, lidovky.cz, e15.cz, echo24.cz, seznamzpravy.cz and aktualne.cz) and asks whether they publish articles about the phenomenon of social enterprises, how often and what information they offer to their readers in these articles. Media are expected to educate society and therefore it is essential to analyse whether their contributions about social enterprises are educational and accurate or rather incorrect or even false. Considering the important role of media in contemporary society, we focused on analysing the media image of social entrepreneurship in Czechia, where the issue of social business is not yet well understood by society. The main goal of the study is to analyse articles with topics of social enterprises and social business published on selected Czech online media and find what kinds of information are provided. A quantitative content analysis of the last six years was used for the research. Results include information about the frequency of publishing, the meaning of the articles, used journalism genres, the role of an advertisement or the role of photos accompanying the written content and so on.